Sex differences in elite swimming with advanced age are less than marathon running - Senefeld, J.; Joyner, M. J.; Stevens, A.; Hunter, S. K. (Scandinavian Journal of Medicine & Science in Sports, 2016)
The sex difference in marathon performance increases with finishing place and age of the runner but whether this occurs among swimmers is unknown. The purpose was to compare sex differences in swimming velocity across world record place (1st-10th), age group (25-89 years), and event distance. We also compared sex differences between freestyle swimming and marathon running. The world's top 10 swimming times of both sexes for World Championship freestyle stroke, backstroke, breaststroke, and butterfly events and the world's top 10 marathon times in 5-year age groups were obtained. Men were faster than women for freestyle (12.4 ± 4.2%), backstroke (12.8 ± 3.0%), and breaststroke (14.5 ± 3.2%), with the greatest sex differences for butterfly (16.7 ± 5.5%). The sex difference in swimming velocity increased across world record place for freestyle (P < 0.001), breaststroke, and butterfly for all age groups and distances (P < 0.001) because of a greater relative drop-off between first and 10th place for women. The sex difference in marathon running increased with the world record place and the sex difference for marathon running was greater than for swimming (P < 0.001). The sex difference in swimming increased with world record place and age, but was less than for marathon running. Collectively, these results suggest more depth in women's swimming than marathon running.